Pengaruh Viscap Brand Ambassador dan Loyalitas Penggemar terhadap Brand Image Scarlett di Media Sosial Tiktok - Merlis Lumeno; Nur Amalyna Yusrin (Penerbit Goodwood, 2024)
Purpose: The objectives of this research are: 1) to determine whether the visibility of Brand Ambassador has an effect on Brand Image; 2) to determine whether the Credibility of the Brand Ambassador has an effect on Brand Image; 3) to determine whether the Attraction of the Brand Ambassador has an effect on Brand Image; and 4) to determine whether the power of brand ambassador influences brand image. 5) to find out whether Fan Loyalty to Brand Ambassadors influences Brand Image, 6) to find out whether VISCAP and Fan Loyalty to Brand Ambassadors influence Brand Image Research methodology: The research method used in this study was quantitative, with multiple linear regression analysis. The samples in this study were obtained using Cochran’s formula to obtain 384 samples. Data collection techniques use questionnaires Results: The research results show that there is an influence of VISCAP and Fan Loyalty which has a significant positive influence on the scarlet whitening brand image on Tiktok social media. The coefficient of determination is 0.573. This means that 57.3% of the variation in the brand image variable for the Scarlet Whitening product can be explained by the variables of Visibility, Credibility, Attraction, Power and Fan Loyalty. Meanwhile, 42.7% of the variation in the Brand Image variable was explained by other variables not discussed in this study. Limitations: In the research that has been carried out, researchers experienced difficulties when searching for sampling theories and also limited time to collect data for data processing. Contribution: The achievements of this research can contribute to Tiktok always paying attention to product excellence and continuing to retain consumers, even though it will use a different brand ambassador.